Pengaruh Model Inkuiri Terbimbing Berbasis Etnosains Pada Pelajaran Sejarah Kebudayaan Islam Terhadap Kemampuan Berpikir Kritis Siswa Kelas IV Di MI Al-Ihsan Mulyasari Banyuasin - Dwi Anjaswati; Middya Boty; Aquami (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low level of critical thinking skills among fourthgrade students in the Islamic Cultural History (SKI) course at MI Al-Ihsan MulyasariBanyuasin. The purpose of this study was to determine the effect of a guided inquirylearning model based on ethoscience on students’ critical thinking skills. This studyused a quantitative approach with a Pre-Experimental One-Group Pretest-PosttestDesign. The research sample consisted of 27 fourth-grade students. Data collectiontechniques included observation, documentation, and test data. Data were analyzedusing normality tests and the Paired-Sample T-Test for hypothesis testing. Theresults showed that the students’ mean pretest score was 62.96 and increased to87.59 on the posttest. The normality test results indicated that the data werenormally distributed, with a significance value of 0.368 for the pretest and 0.632 forthe posttest. Furthermore, the results of the hypothesis test yielded a significancevalue (Sig. 2-tailed) of 0.001 < 0.05, indicating that there is a significant effect ofusing the guided inquiry learning model based on ethoscience on students’ criticalthinking skills. Thus, the guided inquiry learning model based on ethoscience canserve as an effective alternative approach to enhancing students’ critical thinkingskills in the subject of Islamic Cultural History.